Implementation of Training Protocols Addressing Equitable Care in US Student-Run Clinics - Aashka Shah; Nathan Barger; Jessica Ding; Raissa Li; Kuhan Mahendraraj; Shrey Patel; Clinton Pong (Journal of Student-Run Clinics, 2023)
Background: Student-run clinics (SRCs) provide free healthcare to surrounding communities—oftentimes underserved communities. In these clinics, medical students see a wide array of patients under the supervision of physicians. SRCs have helped to fill a gap in primary care and provide an opportunity for students to refine their clinical skills. However, no uniform training program exists across all student-run clinics. This study aims to assess and analyze the quality and characterization of these training programs to inform future trainings and ultimately provide more equitable care to the communities being served by SRCs. Methods: A nine-question survey was sent out by email to 96 clinics across the United States. Upon obtaining data, the study team de-identified the results. Two independent raters coded the survey responses using an inductive approach. Themes were derived from responses and summarized into nominal codes.Results: The populations served by the clinics that responded in decreasing order of magnitude were underinsured/uninsured (83%); immigrant/non-English speaking populations (75%); black, indigenous, and people of color (67%); homeless (67%); low-income (67%); sex workers (17%); youth (8%); and injection drug users (8%). Nine (75%) clinics had some form of training for volunteers and 3 (25%) offered no formal trainings. 75% of all clinics surveyed offered both “cultural competency” and “general introduction to systems training.” The majority of clinics partnered with local hospitals/clinics (50%). Other community partners included mental health and homeless agencies, local pharmacies, and schools. Two (17%) of the clinics surveyed did not have any community partners.Conclusion: SRCs offer a unique solution towards bridging the gap in health inequity in America. The study shows possible gaps in training among schools in the US. Although some schools have adopted formal, standardized training programs, many do not encompass instruction on topics including cultural humility, trauma-informed care, de-escalation, and population-specific care.